“Gestión de cuentas por cobrar en la empresa Artefacta distrito Urdaneta en el periodo 2021” - Castillo Cedeño, Vasti Abigail (2022)
The intention of this research is to examine the management of accounts receivable of the company "Artefacta" Distrito Urdaneta in the period 2021. The methodology used is descriptive, since, contributing to knowing the accounting information of said company, allowing to observe the Study variables related to informative data in decisions such as the management of accounts receivable and their liquidity, in order to determine the annex, they have with each other. Where the effect of accounts receivable management is analyzed, through the activity ratios, where the turnover of accounts receivable and average collection term is involved, as well as the liquidity ratios that include current liquidity, test acid, ratio of cash and net working capital to assets. The company "Artefacta" Urdaneta District, due to the health emergency better known as the Covid 19 coronavirus pandemic, was affected by different scenarios since some payments were not collected on the set dates, which resulted in a high rate of accounts receivable shown in current assets in the company's statement of financial position or balance sheet. After the results obtained, the importance of an optimal application in the management of accounts receivable of the company is evident, since it has a greater incident in its liquidity. In conclusion, the management of accounts receivable has a high incidence on the liquidity of the company, that is, its intervention is an important part when facing financing problems, as well as the activity ratios related to the rotation of accounts receivable and the average collection period, where it is observed that these have a greater impact on current liquidity, because despite achieving the collection of cash, there are still accounts receivable.